2011
DOI: 10.1093/ntr/ntr231
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Phenotypic and Genotypic Associations With Nicotinic Dependence

Abstract: Introduction: Strong evidence demonstrates that nicotine dependence is associated with 4 genetic variants rs16969968, rs6474412, rs3733829, and rs1329650 in large-scale GenomeWide Association Studies. We examined how these identified genetic variants relate to nicotine dependence defined by different categorical and dimensional measures. Methods:Four genetic variants were analyzed in 2,047 subjects of European descent (1,062 cases and 985 controls). Nicotine dependence was assessed with multiple smoking measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 31 publications
1
39
1
Order By: Relevance
“…No previous study analyzed the association of the rs578776/rs3743078 locus with craving. One study showed an association of three related craving measures with CHR-NA5/A3/B4 variant rs16969968 (Chen et al, 2012), which is not consistent with our results showing no association. Another study showed an association of a craving scale with joint haplotypes of variants rs16969968 and rs578776, but only among early-onset smokers (Baker et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…No previous study analyzed the association of the rs578776/rs3743078 locus with craving. One study showed an association of three related craving measures with CHR-NA5/A3/B4 variant rs16969968 (Chen et al, 2012), which is not consistent with our results showing no association. Another study showed an association of a craving scale with joint haplotypes of variants rs16969968 and rs578776, but only among early-onset smokers (Baker et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Although sample sizes were slightly different for the other CHRNA5/ A3/B4 variants (delineated below), demographic proportions were virtually the same. Lifetime smokers had smoked 100 cigarettes, a threshold widely used to indicate substantial smoking (Bondy et al, 2009;Chen et al, 2009Chen et al, , 2012Saccone et al, 2009aSaccone et al, , 2009b. Of these, 82.5% (n = 546) were male; 19.0% (n = 126) were 21-29 years old, 33.1% (n = 219) were 30-44, and 47.9% (n = 317) were 45 years or older; 28.8% (n = 191) were immigrants from the former Soviet Union.…”
Section: Study Procedures and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with the risk allele for rs16969968 selfreport higher levels of nicotine dependence and report consuming more cigarettes per day. [24][25][26][27][28][29] In sum, feedback on genetic susceptibility to nicotine dependence can serve as a "teachable moment" acting as a warning sign to some college smokers, and as an indicator to others, that cessation is easier before addiction sets in. This approach may be most effective among light college smokers.…”
Section: Introductionmentioning
confidence: 99%
“…There is preliminary evidence that the WISDM PDM subscales are related to genetic variants located on CHRNA5-A3-B, which have been previously found to be associated with susceptibility for nicotine dependence. 7,30 Several studies have found mood and anxiety psychiatric diagnosis status to be related to the PDM composite scale and its subscales; and to theoretically relevant SDM subscales reflecting affective, cognitive enhancement, affiliative attachment, and lack of alternative reinforcer motives for smoking in pregnant and nonpregnant samples. [31][32][33][34][35] In a previous study that used the same sample as that of the current study, we found childhood trauma to be predictive of the PDM subscale of Tolerance and several SDM scales, with Negative Reinforcement having the greatest relative contribution to variance.…”
mentioning
confidence: 99%